Detection of interictal epileptiform discharge in focal seizures - Saxena, Shikha; Gupta, Kamal Kant (Nepal Journal of Neuroscience, 2023)
Introduction: Many factors underlying basic epileptic conditions determine the characteristics of epileptic seizures and the therapeutic outcome. Visual obvious abnormalities in resting baseline EEG are cardinal but incompletely understood like feature of seizure onset zone in focal epilepsy and interictal epileptiform discharge. Present study is an attempt to diagnose that evidence of epileptic discharge in temporal lobe epilepsy (TLE), would persist during interictal period in absence of abnormalities in baseline EEG, which could increase the impact of automatic analysis of EEG waves for clinical relevance. Material and Methods: By using 10-20 system, functional connectivity was estimated in the 20 channels of delta, theta, alpha, beta and gamma frequency bands of EEG, from 16 diagnosed focal epileptic seizure patients and 16 age and sex matched controls. To observe the dynamics of the healthy brain, differ from the brain of dynamically focal epileptic patients during interictal period treated with anti-epileptic drugs in the context of resting state during eye close session of EEG. Such differences can be observed by using absolute spectral power from BESS ((Brain Electro Scan Software) of the Axxonet System and statistically measure by applied unpaired student t -test. Result: The high significance results in slow frequency EEG waves (delta and theta) in power spectral analysis were observed that demonstrates the potential epileptic discharge occurring during interictal period without visible pathological activity for helping in the diagnosis and lateralization of TLE. Conclusion: The detailed spectral analysis of EEG waves offers novel insight into focal epileptic patients when visually EEG findings were normal. This linear analysis helpful in extracting information from EEG signals in diagnosing specific neuronal correlates for TLE. Present findings concluded that epileptic discharges occur at different topographical regions of brain during interictal period and power spectral analysis plays a new insight in diagnosis of focal discharge.